Bullous disease after dental implant placement procedure: a case report highlighting clinical aspects - Gilligan, Gerardo Marcelo; Galíndez-Costa, María Fernanda; Moine, Lorena; Sambuelli, Gabriela; Panico, René Luis (Journal of Oral Diagnosis, 2018)
IgA bullous dermatosis (LIgAD) is an uncommon diagnosis in Oral Medicine. The LIgAD- associated oral mucosa involvement was previously described by other authors and the clinical presentation is similar to other bullous diseases such as Pemphigus Vulgaris or other subtypes of Pemphigoids. The aim of this work is to report a case of a 63-years- old male who consulted for several painfully bullous lesions related to a story of non- treated cutaneous and ocular lesions. The patient referred the begin of the disease after a dental implant surgery procedure. The Direct Immunofluorescence allowed to show an IgA deposit in a linear pattern throughout the base membrane zone. After diagnosis, a corticosteroid treatment was applied with a huge improvement and healing of the lesions. This is the first case described in current literature of a rare bullous entity associated with a dental implant placement procedure. Since there was described several trigger factors related to dental practice, there should be more reports of these cases highlighting clinical presentation, therapeutic management and probable trigger factors for this entity.